3D bioprinting optimization of human mesenchymal stromal cell laden gelatin-alginate-collagen bioink. (1st January 2023) - Sawyer, Stephen W; Takeda, Kazuyo; Alayoubi, Alaadin; Mirdamadi, Eman; Zidan, Ahmed; Bauer, Steven R; Degheidy, Heba
Abstract: 3D bioprinting technology has gained increased attention in the regenerative medicine and tissue engineering communities over the past decade with their attempts to create functional living tissues and organs de novo . While tissues such as skin, bone, and cartilage have been successfully fabricated using 3D bioprinting, there are still many technical and process driven challenges that must be overcome before a complete tissue engineered solution is realized. Although there may never be a single adopted bioprinting process in the scientific community, adherence to optimized bioprinting protocols could reduce variability and improve precision with the goal of ensuring high quality printed constructs. Here, we report on the bioprinting of a gelatin-alginate-collagen bioink containing human mesenchymal stromal cells (hMSCs) which has been optimized to ensure printing consistency and reliability. The study consists of three phases: a pre-printing phase which focuses on bioink characterization; a printing phase which focuses on bioink extrudability/printability, construct stability, and printing accuracy; and a post-processing phase which focuses on the homogeneity and bioactivity of the encapsulated hMSC printed constructs. The results showed that eight identical constructs containing hMSCs could be reliably and accurately printed into stable cross-hatched structures with a single material preparation, and that batch-to-batch consistency was accurately maintained across all preparations. Analysis of the proliferation, morphology, and differentiation of encapsulated hMSCs within the printed constructs showed that cells were able to form large, interconnected colonies and were capable of robust adipogenic differentiation within 14 d of culturing.